Effects of relocating an inpatient programme for the "difficult-to-place" mentally ill, from a hospital to a community setting : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, Massey University - Daldy, Robert (Massey University, 1999)
In order to effect final closure of Lake Alice Hospital, the need for a special inpatient facility for the ongoing treatment of a residual "long-stay" patient population was recognised. The Intensive Learning Centre (ILC) was developed to cater for this group, that were "difficult-to-place" by virtue of their unsuitability for existing trust and sheltered accommodation in the community. Consistent with the long-term plan, the programme was relocated from the hospital grounds to a community setting at Castle Cliff, Wanganui, continuing operation as Endeavour Lodge. The present research had three principal aims: to determine effects of relocation on the original ILC programme; to assess the functioning of the current Endeavour Lodge client group in order to extend findings from previous research; and to make a formal characterisation of the prevailing "Ward Atmosphere" or therapeutic milieu, in the new community location. A comparison of the two programmes was made on the basis of information gained from semi-structured staff interviews, and reviews of programme operating manuals and previous research. Client functioning was assessed with the use of two informant driven measures; the Rehabilitation Evaluation Hall and Baker (REHAB) and the Adaptive Behaviour Scale (ABS). Characterisation of the therapeutic milieu was made with the Ward Atmosphere Scale (WAS-R). It was found that relocation coincided with a loss of key personnel responsible for the development of the original ILC programme, who had experience and expertise in the use of "Behaviour Modification" techniques. Formal behavioural modification strategies that were an integral part of the original ILC prescription, appeared to have fallen into comparative disuse at the time of the current study. An initial significant improvement in general functioning was found between baseline and the 5- month follow-up. No other significant change in functioning was identified for either general functioning or maladaptive behaviour, between any of the subsequent follow-up periods. However, a descriptive supplemental analysis of mean group total scores, did identify meaningful and consistent trends of behaviour change over time. The implications of the findings, and recommendations for the programme and future research are discussed.
Keywords: Community mental health services; Endeavour Lodge; Wanganui, New Zealand